Understanding policy alignment in addressing hydrological hazards in the Niger Delta region, Nigeria - Obroma O. Agumagu; Robert Marchant; Lindsay C. Stringer (PLoS ONE, 2026)
Combating climate change, flood risk, managing land use, and developmental change need cohesive policy action. Analysing policies is essential to assess whether there is a coherent approach where various sectors support each other, or at least do not conflict. This study analyses policy documents addressing hydrological hazards in the Niger Delta region, Nigeria using Qualitative Document Analysis, content analysis, keyword analysis and frequency counts. These insights were used to examine: 1) the types of hydrological hazards and their drivers recognised in six national policy documents across environment, climate change, agriculture, water, forest, and petroleum policy sectors, 2) the measures outlined to reduce the risks from these hazards, and 3), how well aligned the measures are across sectors for management of the Niger Delta region. Results reveal that the policies across the Environment and Climate Change directly address hydrological hazards and their climatic drivers. In contrast, Agriculture, Water, and Forest policies demonstrate sector-specific approaches, while the Petroleum policy stands out for its very limited consideration of hydrological hazards and their drivers. Hydrological hazards were considered as high rainfall, river floods, sea level rise, storm surges, and warming trends as key hydrological hazards. Climate variability and human activity arising from urbanisation, deforestation, industrialisation, agriculture, and population are identified as drivers that can exacerbate the hazards and their impacts. Measures across the policies consider flood defence structures, preparing comprehensive hazard maps and vulnerability analysis to strengthen smart water management to reduce risk and build adaptive capacity across the region. Overall alignment of the six national policies is found to be low, indicating limited attention to the interactions between sectors and stakeholders. This pattern indicates horizontal misalignment. For Nigeria to better manage climate change impacts, all hydrological hazards and their drivers must be recognised. There is a need for the policy framework to be more joined-up so that a multi-sector approach can reduce risks from hydrological hazards.